Essentials of positioning and location technology - Bartlett, David, 1958- (Cambridge : Cambridge University Press, 2013)
'Mystified by locating and positioning technologies? Need to get the best from your location system? This guide is invaluable for understanding how the positions and movements of objects can be measured and used for real-world applications. From it, you'll learn how to optimise and manage system performance by working with parameters such as velocity, orientation, time, proximity and direction, and consider not only accuracy, but also reliability, integrity, response time and uncertainty. Packed with practical examples, this concise book gives you an overview of terrestrial radiolocation techniques, including comparative system architectures and real-world performance and limitations. It describes inertial navigation principles and techniques, including low-cost MEMS sensors for consumer products, and a range of applications, such as those benefiting from hybrid positioning techniques'--
Machine generated contents note: 1. Introduction to location; 2. Coordinate systems; 3. Satellite positioning (GNSS); 4. Radiolocation technologies; 5. Inertial navigation; 6. Other techniques and hybrid systems; 7. Techniques and performance; 8. When things go wrong; 9. Location based services and applications; 10. A brief look at the future.
Includes bibliographical references (pages 193-197) and index.
Keywords: Location-based services; Mobile geographic information systems